(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Topsoil erosion is the most common issues in today’s world related to soil distresses. Soil erosion can cause contamination of drinking water, disturbs ecosystem of lakes and other water bodies and can cause landslides problems in hilly regions. It becomes necessary to prevent soil erosion by using some methods. This project discusses to prevent soil erosion by using jute mats or jute sacks in hilly regions. For this project work we have choose the nearby hill of Bhimber Gali which has experienced landslide in recent days. After that, we have to prepare the box model of dimensions 150cm*50cm*40cm to show all the site properties such as field density, moisture content etc. in physical modeling. Moreover, it is needed to measure slope inclination of the hill by help of theodolite surveying and prepare same slope in box model. Then, rainfall data analysis is necessary for simulation of rainfall in laboratory for this we have to take rainfall data of Poonch district of J&K for last 5 years. Further then, scaling of model dimensions and rainfall data is done accordance with the need. Then simulation of rainfall must be done in laboratory by calibrating according to the scaling value of rainfall intensity and simulation of rainfall must be done by applying jute mats and steel fence as well as without applying them. After simulation of rainfall we have to measure soil erosion by the help of runoff collector method as well as we have to examine the slope changes and slope failure, if happen. Further then, if slope failure of box model not take place by applying jute mats then examine the slope changes or failure at different intensities greater than given district rainfall intensity.